Utilizing an explanatory case method approach to explore alternative recruitment strategies for a longitudinal randomized clinical trial of insomnia treatment in cancer survivors amid COVID-19 - Suzanne S. Dickerson; Karen P. Larkin; Dianne Loomis; Donna Tyrpak; Misol Kwon; Youngran Cha; Heba Mohedat; Grace E. Dean (PLoS ONE, 2025)
COVID-19 was a barrier to meeting recruitment goals in clinical trials particularly for behavioral interventions requiring innovative and evolving strategies. This paper explores recruitment approaches prior to, during, and after the in-person recruitment pause in a longitudinal randomized controlled trial (RCT) in which cancer survivors received one of two interventions to self-manage insomnia. An explanatory case study method was used to investigate pre, during, and post COVID-19 recruitment during a longitudinal RCT. Data analysis included descriptive frequencies of enrollment approaches and outcomes obtained from the research team’s weekly documented recruitment activities, and qualitative analysis of post-recruitment focus group of clinical partner experiences within the environmental context of the clinic settings. Team analysis included data triangulation between research team’s recruitment data and clinical staff experiences, and times series analysis with explanation building with team consensus on the final product. A total of 136 heterogenous cancer survivor participants were recruited utilizing both in-person and virtual strategies with an 87.5% retention rate. Variability in success of recruitment approaches over time was demonstrated within the environmental contexts. Overall, in-person recruitment was the most effective strategy (55.1%) followed by passive strategies of print outreach and social media (36.8%). A creative and persistent research team was needed to achieve the recruitment target with a high retention rate. Recruiting in-person post COVID-19 was challenging due to clinical staff barriers. The explanatory case study method offers insight into the complex recruitment process and potential approaches that could be implemented for future public health insomnia treatment studies.